Cardiovascular outcomes among patients with castration‐resistant prostate cancer: A comparative safety study using US administrative claims data. Issue 7 (6th March 2023) - Conover, Mitchell M.; Weaver, James; Fan, Bo; Leitz, Gerhard; Richarz, Ute; Li, Qing; Gifkins, Dina
Abstract: Background: Cardiovascular conditions are the most prevalent comorbidity among patients with prostate cancer, regardless of treatment. Additionally, cardiovascular risk has been shown to increase following exposure to certain treatments for advanced prostate cancer. There is conflicting evidence on risk of overall and specific cardiovascular outcomes among men treated for metastatic castrate resistant prostate cancer (CRPC). We, therefore, sought to compare incidence of serious cardiovascular events among CRPC patients treated with abiraterone acetate plus predniso(lo)ne (AAP) and enzalutamide (ENZ), the two most widely used CRPC therapies. Methods: Using US administrative claims data, we selected CRPC patients newly exposed to either treatment after August 31, 2012, with prior androgen deprivation therapy (ADT). We assessed incidence of hospitalization for heart failure (HHF), ischemic stroke, and acute myocardial infarction (AMI) during the period 30‐days after AAP or ENZ initiation to discontinuation, outcome occurrence, death, or disenrollment. We matched treatment groups on propensity‐scores (PSs) to control for observed confounding to estimate the average treatment effect among the treated (AAP) using conditional Cox proportional hazards models. To account for residual bias, we calibrated our estimates against a distribution of effect estimates from 124 negative‐control outcomes. Results: The HHF analysis included 2322 (45.1%) AAP initiators and 2827 (54.9%) ENZ initiators. In this analysis, the median follow‐up times among AAP and ENZ initiators (after PS matching) were 144 and 122 days, respectively. The empirically calibrated hazard ratio (HR) estimate for HHF was 2.56 (95% confidence interval [CI]: 1.32, 4.94). Corresponding HRs for AMI and ischemic stroke were 1.94 (95% CI: 0.90, 4.18) and 1.25 (95% CI: 0.54, 2.85), respectively. Conclusions: Our study sought to quantify risk of HHF, AMI and ischemic stroke among CRPC patients initiating AAP relative to ENZ within a national administrative claims database. Increased risk for HHF among AAP compared to ENZ users was observed. The difference in myocardial infarction did not attain statistical significance after controlling for residual bias, and no differences were noted in ischemic stroke between the two treatments. These findings confirm labeled warnings and precautions for AAP for HHF and contribute to the comparative real‐world evidence on AAP relative to ENZ.